Dynamic Politics in The Election of Regional Head (Ogan Komering Ulu Timur Regency in 2020) - Widia Novita Lukitasari. WA (Universitas Medan Area, 2022)
The presence of political dynasties in power struggles from regional to national level is inseparable from the role of political parties and the regulation of the regional head elections. Oligarchy on the body of a political party can be seen from the tendency of candidates nominating by political parties based more on the wishes of party elites, not through democratic mechanisms by considering the ability and integrity of the candidates. Simultaneously, political dynasties continue to establish solid networks of power so they can dominate and kill democracy within political parties. In the context of society, there is also an effort to maintain the status quo in the region by encouraging families or people close to the head of the region to replace the incumbent. Weak regulation to trim political dynasties has contributed to the widespread political dynasty in the regional head elections. The practice of dynastic politics is also suspected to make the weakness of checks and balances function to the effect of corruption acts committed by the head of the region and their relatives. The regional head elections system is new, but the old faces that are nothing but the continuity of the political dynasty characterize this Pilkada event which is feared could threaten the phase of democratic transition towards consolidation of democracy.